Cardiopulmonary physiotherapeutic application of taiji. - Klein PJ; Adams W (Cardiopulmonary Physical Therapy Journal (American Physical Therapy Association, Cardiopulmonary Section), 2004)
Problem: Taiji practice is known to have health benefits. As a therapeutic exercise, it may have potential applications in cardiopulmonary physical therapy (PT). Methods: To explore this possibility, a systematic critical review of the topic-related literature was conducted. Results: One hundred fifty-six original articles were examined, yielding 7 controlled clinical studies with primary relevance to cardiopulmonary practice. Critical review of these studies revealed that regular practice of taiji has potential cardiovascular benefits in the areas of improved submaximal activity tolerance, blood pressure control, and enhanced immune response. Discussion: Sufficient research evidence is available to explore programming options in PT cardiopulmonary practice. Additional potential applications may exist in the areas of pulmonary rehabilitation, peripheral vascular insufficiency, diabetic management, and early mobilization post medical or surgical event. Implications: Information presented should help inform PT clinicians of the potential benefits of integration of taiji practice with more traditional cardiopulmonary rehabilitative modalities. It also should provide impetus for innovational program planning and consideration of inclusion of taiji as a therapeutic exercise as part of professional or continuing education curricula.